(untitled) (Fiep Bulletin - online, 2014)
During a game of indoor soccer, the teams use many stock-technical tactics aimed at building advantageous terms on the opponent. In indoor soccer, there is a clear need to raise the level of effectiveness of offensive actions, including the counter-attack, thus allowing a greater number of opportunities for goal. This study aimed to determine the frequency of cases of counter-attack in the games of indoor soccer and his effectiveness, and analyze the technical and tactical behaviour occurred during the counter-attacks, in games of indoor soccer. The sample of the study was composed of 13 games from the V Brazilian Championship - Selections, category sub-15. From the observation of these games, were collected and analyzed through a spreadsheet of observation, the behaviour technical-tactical achieved by players in situations of counter-attack. The technique was used for observation of the analysis focused on the game and for treatment of the data was used a descriptive analysis. After processing the data, it was observed that of the 442 cases of counter-attacks, 182 (26%) resulted in finalizations against the opponent goal, and that these 182 finalizations, 24 (33%) were led in goals, and the effectiveness of completion (13.2%). It was possible to see, too, that the counterattacks used predominantly numerical equality as functional structure (54%), and that the sector that occurred in the largest percentage of origin of the counter-attacks was the intermediary sector defensive (42%). Thus, it is concluded from the present study that the counter-attacks, mostly, using the same number as functional structure, had commenced in the middle-court defensive, and has the final result, the completion.